Implementación de un sistema de costos para las microempresas de fabricación de bloques en el sector la Cangahua, Parroquia Belisario Quevedo - Trávez Avilés, Sally Dayana (2019)
The present project was focused on the cost system for the micro-enterprises of bricks manufacturing in the Cangahua zone, Belisario Quevedo parish, because of a diagnosis made by students in a previous research, it was demonstrated that the microenterprises do not have control of the costs incurred in the finished products in the Cangahua zone, reflecting that there was a lack of knowledge about the real cost of production and the value of utility in sales. The objectives of this project consisted in gathering information about input costs of these microenterprises, designing the systematic platform in Excel spreadsheets through Visual Basic for Applications and systematize the information within this system. The methodology was based on a descriptive and explanatory research supported by a field investigation, for which it was necessary to use data collection tools such as interviews and field visits to the owners of the different microenterprises. The implementation of the cost system allowed to identify and generate competitive strategies and production options, among the most important it was found that when producing combined boards (bricks of two measures) the production cost of the most measured product is reduced by approximately 40 % of its normal cost, unlike using individual boards. Additionally, the digitalization of the information will allow the creation and maintenance of organized records of easy access to a database, which will help the owner to identify periods of low commercialization in previous periods.